Novel missense mutation in the RSPO4 gene in congenital hyponychia and evidence for a polymorphic initiation codon (p.M1I) - Khan Tahir; Klar Joakim; Nawaz Sadia; Jameel Muhammad; Tariq Muhammad; Malik Naveed; Baig Shahid M; Dahl Niklas (BMC, 2012)
Abstract Background Anonychia/hyponychia congenita is a rare autosomal recessive developmental disorder characterized by the absence (anonychia) or hypoplasia (hyponuchia) of finger- and/or toenails frequently caused by mutations in the R-spondin 4 (RSPO4) gene. Methods Three hypo/anonychia consanguineous Pakistani families were ascertained and genotyped using microsatellite markers spanning the RSPO4 locus on chromosome 20p13. Mutation screening of the RSPO4 gene was carried out by direct sequencing of the entire coding region and all intron-exon boundaries. Results Mutations in the RSPO4 gene were identified in all families including a novel missense mutation c.178C>T (p.R60W) and two recurrent variants c.353G>A (p.C118Y) and c.3G>A (p.M1I). The c.3G>A variant was identified in unaffected family members and a control sample in a homozygous state. Conclusions This study raises to 17 the number of known RSPO4 mutations and further expands the molecular repertoire causing hypo/anonychia. The c.353G>A emerges as a recurrent change with a possible founder effect in the Pakistani population. Our findings suggest that c.3G>A is not sufficient to cause the disorder and could be considered a polymorphism.